2004
DOI: 10.1158/1078-0432.ccr-03-0651
|View full text |Cite
|
Sign up to set email alerts
|

The A3 Adenosine Receptor Is Highly Expressed in Tumor versus Normal Cells

Abstract: Purpose: A 3 adenosine receptor (A 3 AR) activation was shown to inhibit the growth of various tumor cells via the down-regulation of nuclear factor B and cyclin D1. To additionally elucidate whether A 3 AR is a specific target, a survey of its expression in tumor versus adjacent normal cells was conducted.Experimental Design: A 3 AR mRNA expression in various tumor tissues was tested in paraffin-embedded slides using reverse transcription-PCR analysis. A comparison with A 3 AR expression in the relevant adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 18 publications
10
128
0
Order By: Relevance
“…It is reported that the skeletal muscle microenvironment reduces cancer cell tumorigenicity and elicits paracrine-mediated cytotoxic and cytostatic responses from metastatic cancer cells (30). In particular, several studies identified the A 3 adenosine receptor (A 3 AR), which is expressed by multiple cancer cell types (31), as key in the antimetastatic and protective effect of skeletal muscle cells (32). Before investigating the role of A 3 AR in extravasation, we first demonstrated through immunofluorescence that BOKL introduced in our system expressed the A 3 AR (Fig.…”
Section: Generation Of Functional 3d Microvascular Network Within a Bmimentioning
confidence: 99%
“…It is reported that the skeletal muscle microenvironment reduces cancer cell tumorigenicity and elicits paracrine-mediated cytotoxic and cytostatic responses from metastatic cancer cells (30). In particular, several studies identified the A 3 adenosine receptor (A 3 AR), which is expressed by multiple cancer cell types (31), as key in the antimetastatic and protective effect of skeletal muscle cells (32). Before investigating the role of A 3 AR in extravasation, we first demonstrated through immunofluorescence that BOKL introduced in our system expressed the A 3 AR (Fig.…”
Section: Generation Of Functional 3d Microvascular Network Within a Bmimentioning
confidence: 99%
“…These antitumour effects might be counteracted to some extent by adenosine, produced after breakdown of ATP by ectonucleotidase, which is known to promote proliferation of tumour cells, as well as acting as an immunosuppressant [32][33][34][35][36]. However, adenosine has also been shown to have anti-tumour effects by inhibiting tumour growth via A 3 receptors [37][38][39] or by inhibiting apoptosis [40]. Further studies are needed to resolve these contradictory issues.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting gene, SMO, is a known oncogene for basal cell carcinoma (14) that activates the Hedgehog pathway, leading to an increase in angiogenic factors (15), cyclins D1 and B1 (16), and antiapoptotic genes, and a decrease in apoptotic genes (FAS) (17). In addition, ADORA3, an adenosine receptor, has been observed to be highly expressed in a variety of tumors and has been suggested as a potential therapeutic target (18).…”
Section: Genes With a Restricted Expression In Normal Tissues And Difmentioning
confidence: 99%